Strategy for Using Information Technology for Learning Minahasa Culinary Specialties - Tangkere, Telly (International Journal of Information Technology and Education, 2024)
This study explores the strategy of using information technology (IT) in learning Minahasan culinary, a region with a rich and diverse culinary heritage in Indonesia. Given the importance of preserving traditional culinary culture, this study aims to identify how technology can support the learning process in formal and non-formal educational institutions. The research methods used include surveys, in-depth interviews, and case study analyses of various learning programs implementing information technology as a learning medium. The results of the study indicate that the use of technology such as mobile applications, e-learning platforms, and social media is effective in increasing the accessibility and understanding of students towards traditional Minahasan culinary recipes and techniques. In addition, integrating technology into learning can facilitate interaction between instructors and students and encourage innovation in the presentation and development of traditional recipes. This study provides recommendations for teachers and curriculum developers to optimize the use of technology in traditional culinary learning, to ensure the preservation of Minahasan culinary culture in the digital era